2017
DOI: 10.18054/pb.v119i1.4407
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dietary mannan oligosaccharide and clinoptilolite on hematological, biochemical and gut histological parameters in weaned pigs

Abstract: Background and Purpose: Yeast derivative mannan oligosaccharide (MOS) and zeolite clinoptilolite (CPL) well known nutritional supplements acting as either prebiotic or immunobiotic, respectively, in animal husbandry. The aim of this study was to investigate whether or not these agents referred to as potential alternatives to antibiotics may positively influence systemic immune parameters of weaned pigs without negatively affecting their hematological, serum biochemical and gut histological homeostasis. Materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(38 reference statements)
1
10
1
Order By: Relevance
“…Similarly, supplementation dietary MOS did not affect the WBC count, HCT, neutrophil count, mononuclear leukocyte count, or eosinophil count of dairy cows or their offspring ( Franklin et al, 2005 ). Other studies on the effects of MOS in monogastric animals have reported similar results: supplementation dietary MOS did not impact RBC count, hemoglobin, HCT, or MCHC of weanling pigs in one study ( Valpotić et al, 2017 ; Dos Anjos et al, 2019 ), or RBC count, WBC count, lymphocyte count, or diarrhea score in another study ( Zhao, Jung & Kim, 2012 ), and did not influence monocyte, basophil, or eosinophil counts in Arbor Acres broiler chickens ( Attia et al, 2017 ).…”
Section: Discussionsupporting
confidence: 54%
“…Similarly, supplementation dietary MOS did not affect the WBC count, HCT, neutrophil count, mononuclear leukocyte count, or eosinophil count of dairy cows or their offspring ( Franklin et al, 2005 ). Other studies on the effects of MOS in monogastric animals have reported similar results: supplementation dietary MOS did not impact RBC count, hemoglobin, HCT, or MCHC of weanling pigs in one study ( Valpotić et al, 2017 ; Dos Anjos et al, 2019 ), or RBC count, WBC count, lymphocyte count, or diarrhea score in another study ( Zhao, Jung & Kim, 2012 ), and did not influence monocyte, basophil, or eosinophil counts in Arbor Acres broiler chickens ( Attia et al, 2017 ).…”
Section: Discussionsupporting
confidence: 54%
“…In the functional study using the CPL-fed mice as the immune cell donors immunostumulatory effect of the agent was also observed (37). Regarding limited reports on potential adverse effects of CPL as a feed supplement, tested in pigs (19) it has been shown that the agent was not associated with any harmful side effects on monitored blood and gut histological parameters as well on impairment of general health status of pigs.…”
Section: Frey Et Al (42)mentioning
confidence: 92%
“…Therefore, zeolites have been recognized as interesting nanoporous materials and became subjects of research in different areas of chemistry, and are now widely used in industrial, agricultural, environmental and biological technologies (13,33), but have also attracted interest for use in molecular medicine (26). Several toxicological studies as well as hematological, biochemical and histopathological analyses of a natural CPL proved that this compound is non-toxic and safe for use in human and veterinary medicine (19,25,31,(34)(35)(36). The CPL utilization in veterinary medicine showed that it is capable to act as detoxificating (including mycotoxins and heavy metals), antioxidant, hemostatic, anti-diarrheic, growth-promoting and immunostimulating agent (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is a very interesting compound on the medical market and has recently been approved in the EU as a feed additive for use as a mycotoxin binder in veterinary medicine, particularly in the livestock, swine and poultry industry (VALPOTIĆ et al, 2017a;VALPOTIĆ et al, 2017b;VALPOTIĆ et al, 2018). In addition, recently, ĐURIČIĆ et al (2017) evaluated the effects of dietary clinoptilolite (CPL), a novel vibroactivated and micronized modification (Vibrosorb) of the natural mineral, in lactating dairy cows, on milk composition, SCC and the incidence of subclinical mastitis from the third to the seventh month of gestation.…”
Section: Prevention and Therapy Of Mastitismentioning
confidence: 99%